Circulating IL-17 Level Is Positively Associated with Disease Activity in Patients with Systemic Lupus Erythematosus: A Systematic Review and Meta-Analysis. (21st July 2021) - Yin, Rulan; Xu, Rong; Ding, Lei; Sui, Wenjie; Niu, Mei'e; Wang, Mingjun; Xu, Lan; Wang, Haifang; Srirat, Chomphoonut
Abstract : Previous studies on the relationship between the circulating level of interleukin-17 (IL-17) and disease activity in systemic lupus erythematosus (SLE) were contradictory. This study is aimed at quantitatively assessing the correlation between the circulating IL-17 level and disease activity in SLE patients. A systematic search for related literature was conducted via PubMed, Web of Science, EMBASE, and Cochrane Library (up to January 26, 2021). The relationship between circulating IL-17 levels and SLE activity was evaluated using Fisher's z value, which was then converted to r . The standardized mean difference (SMD) and its 95% confidence interval (CI) were used to describe the difference between the circulating IL-17 level in patients with active and inactive SLE. STATA 16.0 was used to perform statistical analysis. Random-effects model was performed to synthesize data. Twenty-six studies involving 1, 560 SLE patients were included in this review. The pooled r value was 0.38 (95% CI: 0.25-0.50; I 2 = 83.8 %, P < 0.001 ) between the SLE activity and circulating level of IL-17. Patients with active SLE had higher level of circulating IL-17 than that of inactive (pooled   SMD = 0.95, 95% CI: 0.38-1.53; I 2 = 90.5 %, P < 0.001 ). The subgroup analysis suggested that the region and detection method of circulating IL-17 might not be a source of heterogeneity. No significant publication bias was found. In summary, circulating IL-17 level has a low positive relationship with SLE activity. It is necessary to carefully consider the use of circulating IL-17 as a biomarker of the disease activity in SLE patients. The relationship between the circulating level of IL-17 and SLE activity should be further confirmed in randomized controlled studies.